"China, why not?": serious leisure and transmigrant runners' stories from Beijing. Issue 3 (4th May 2017) - Ronkainen, Noora J.; Harrison, Marlen; Shuman, Amanda; Ryba, Tatiana V.
Abstract: The purpose of this study was to examine how amateur, serious distance runners negotiate their running practices upon transnational migration to China. Despite the extensive body of research into expatriate experiences and adaptation, serious leisure as a site where meaning-making occurs has not been studied in existing research. Through interviews with five female and two male expatriates, we studied the ways in which Western runners brought meaning to the transition experience and negotiated meanings and bodily practices associated with running. Through narrative analysis, we identified three core narratives of migration (possibility, necessity and growing up) and two emergent narratives (community and running to feel like oneself) about shifting meaning in running. We conclude with implications for future research in serious leisure and migration studies.